2019
DOI: 10.1080/00325899.2019.1625186
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on microstructure and high strain rate behaviour of pure tantalum prepared by hot press and subsequent annealing treatment

Abstract: Among refractory metals, tantalum has long been the primary material of use in high strain rate applications. Hot pressing (HP) is a technique to produce specimens with high density and homogeneous microstructure. The individual effect of the HP or annealing heat treatment on high strain rate properties of tantalum powder compacts has been investigated, but little attention has been paid to the combined effect of subsequent annealing. In this study, the effect of annealing on the microstructure and mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…It can be observed that the proportion of the <110> texture decreased after vacuum annealing, while the proportion of the <100> texture increased. This indicates that recrystallization occurred in SLMed pure tantalum with the vacuum heat temperature exceeding the recrystallization temperature (about 1100 • C) [18,37]. The grain size of SLMed pure tantalum significantly increased after vacuum annealing at 1600 • C, as shown in Figure 11b.…”
Section: The Effect Of Vacuum Heat Treatments On Mechanical Propertiesmentioning
confidence: 85%
See 1 more Smart Citation
“…It can be observed that the proportion of the <110> texture decreased after vacuum annealing, while the proportion of the <100> texture increased. This indicates that recrystallization occurred in SLMed pure tantalum with the vacuum heat temperature exceeding the recrystallization temperature (about 1100 • C) [18,37]. The grain size of SLMed pure tantalum significantly increased after vacuum annealing at 1600 • C, as shown in Figure 11b.…”
Section: The Effect Of Vacuum Heat Treatments On Mechanical Propertiesmentioning
confidence: 85%
“…In addition, they also pronounced that the decomposition of α martensite after heat treatment in the solar furnace was influenced by temperatures and was different between the top and middle areas [17]. Alaei Moeen et al found that dislocation density, microhardness, and yield strength decreased, but plasticity increased with the temperature being elevated from 1100 • C to 1400 • C for 4 h [18]. Zhou Libo et al studied a three-stage heat treatment for SLMed Ta, with 1800 • C for 2 h, 1600 • C for 2 h, and 1400 • C for 2 h subsequently, which resulted in a transformation from columnar crystals to equiaxed crystals, including a sub-grain dislocation microstructure and tensile elongation that increased from 2% to 12% [19].…”
Section: Introductionmentioning
confidence: 99%